Detection of cytokines in cervicovaginal lavage in HIV-infected women and its association with high-risk human papillomavirus - Schindler, Sandra; Netto, Eduardo; Deminco, Felice; Figueiredo, Camila A.; de Andrade, Candace Machado; Alves, Amanda Rosa; Brites, Carlos (Frontiers in Immunology, 2024)
Cervical cancer is the third most common cancer in women living in developing countries and is associated with human papillomavirus (HPV). Inflammation is the first mucosal defense mechanism and involves the release of cytokines and chemokines, which activate the innate immune response and restore balance to the lower genital tract, but in women living with HIV/AIDS (WLHA), despite access to the new generation of antiretroviral therapy, we observed greater persistence of HPV infection, greater prevalence of cervical intraepithelial neoplasia and greater risk of cervical cancer when compared with the HIV-uninfected population. The host's immune response is, therefore, decisive and changes in CD 4 T cells, the main target of HIV, can negatively modulate the response of specific subgroups of cells, generating an environment conducive to tumor development. Changes in the concentration of some cytokines have been associated with cervical cancer, suggesting a predominance of the Th2 response in WLHA. The objective of this study is to evaluate the concentrations of different cytokines involved in the local immune response in WLHA, which is fundamental for understanding the pathogenesis of HPV related cancer in this population and to develop new strategies to prevent not only cervical cancer, but also other non-AIDS-defining cancers.